3-Aminopropyltriethoxysilyl functionalized Na-Al-MCM-41 solid base catalyst for selective preparation of 2-phenylpropionitrile from phenylacetonitrile - Venkatesan, C.; Chidambaram, M.; Singh, A. P. (Applied Catalysis A-General, 2005)
Various solid base catalysts have been prepared by ion exchange of zeolites and Na-Al-MCM-41 and by organosilane grafting over mesoporous materials. Base catalysts thus synthesized were studied in the selective monomethylation of phenylacetonitrile (PAN) to 2-phenylpropionitrile (2-PPN) using dimethylcarbonate (DMC) as an alkylating agent in a Parr autoclave at a temperature ranging between 443 and 473 K and at autogenously developed pressure. NH2-Na-Al-MCM-41 (30) showed a high activity, and the optimum loading of 3-aminopropyltriethoxysilyl (3-APTES) was found to be 1.35 mmol g(-1), being consistent with the structural characterization. Co-condensation of 3-APTES, tetraethylorthosilicate (TEOS) and sodiumaluminate in the presence of surfactant provides a material with uniformly distributed basic sites responsible for high activity in the selective monomethylation of phenylacetonitrile. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 2-phenylpropionitrile; base catalysis; dimethylcarbonate; monomethylation; NH2-Na-Al-MCM-41; phenylacetonitrile

Organosilanesulfonic acid-functionalized Zr-TMS catalysts: synthesis, characterization and catalytic applications in condensation reactions - Chidambaram, M.; Venkatesan, C.; Singh, A. P. (Applied Catalysis A-General, 2006)
Organosilanesulfonic acid (-Si-R3S-R4SO3H, OSA)-functionalized mesoporous Zr-TMS (Zr-TMS-Si-R3S-R4SO3H, Zr-TMS-OSA) was synthesized either by post-synthetic modification of Zr-TMS (zirconia-based transition metal oxide mesoporous molecular sieves) with 3-mercaptopropyltrimethoxysilane (3-MPTS) and further with 1,4-butanesultone (1,4-BS) or by in situ one-pot synthesis procedure. A number of physico-chemical characterization techniques have been used to show that the organosilanesulfonic acid groups were anchored on to the walls of Zr-TMS. MCM-41-Si-R3S-R4SO3H-20 (MCM-41-OSA-20) was also prepared by post-synthesis procedure for comparison. Physico-chemical properties of in situ made A-Zr-OSA-20, Zr-TMS-SO3H-20 and MCM-41-OSA-20 were compared with Zr-TMS-OSA catalysts. The catalytic activity of the materials was tested in liquid phase condensation of aniline with p-formaldehyde to 4,4'-diaminodiphenylmethane (4,4'-DADPM). Results showed that Zr-TMS-OSA catalysts were more active than Zr-TMS-SO3H-20, MCM-41-OSA-20 and A-Zr-OSA-20 and more selective than Zr-TMS-SO3H-20 and A-Zr-OSA-20 catalysts. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: Acid catalyst; condensation of aniline; mesoporous ZrO2; organic functionalization; organosilanesulfonic acid